2015
DOI: 10.1155/2015/949620
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Differences in Clinical Profile and Biochemical Parameters in Patients with Cushing’s Disease: A Single Center Experience

Abstract: Cushing's disease (CD) is remarkably prevalent among females; however, more severe clinical presentation and adverse outcomes have been found in males. The purpose of this study was to investigate the overall clinical profile and biochemical parameters in patients with CD to identify the gender differences. Here we describe our series of CD patients referred to our medical center during 2012-2013. Among 73 cases, females presented a marked preponderance compared to males. Males had significantly higher ACTH, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
(54 reference statements)
4
12
1
Order By: Relevance
“…A major strength of this study is that it includes a large cohort from two centers and focuses on a broad spectrum of potential differences between sexes, thereby allowing a more accurate description and clear understanding of the clinical picture of ACTH-dependent Cushing's syndrome based on sex, than previous cohort studies. The differences in biochemistry and morbidity found in this study are largely in line with previous studies: higher plasma ACTH (9, 1214), more often anemia (16) and osteoporosis (with fractures) (8, 1113). The lack of difference in etiology and pituitary tumor size was in agreement with some studies (9, 12), but not with others (8, 11).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A major strength of this study is that it includes a large cohort from two centers and focuses on a broad spectrum of potential differences between sexes, thereby allowing a more accurate description and clear understanding of the clinical picture of ACTH-dependent Cushing's syndrome based on sex, than previous cohort studies. The differences in biochemistry and morbidity found in this study are largely in line with previous studies: higher plasma ACTH (9, 1214), more often anemia (16) and osteoporosis (with fractures) (8, 1113). The lack of difference in etiology and pituitary tumor size was in agreement with some studies (9, 12), but not with others (8, 11).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the female preponderance is not yet present in prepubertal cases, suggesting that males are diagnosed with Cushing's syndrome at a younger age (9, 10). This is confirmed by some studies in adults with Cushing's syndrome (11, 12), but rejected by others (13, 14). Some cohort studies have reported males to have more severe clinical presentation (higher body mass index and waist circumference, reduced libido and sexual dysfunction, more striae, myopathy, and hypokalemia), biochemical parameters (higher ACTH, serum cortisol, and urinary free cortisol [UFC] concentrations), complications at diagnosis (higher HbA1c concentrations, more often hypertension, anemia, spine osteoporosis with vertebral fractures, rib fractures, and hypercoagulable state), and worse outcome after surgery (more often anemia, lower cortisol normalization rate, and higher recurrence rate), than females (8, 9, 1116).…”
Section: Introductionsupporting
confidence: 56%
“…From a clinical viewpoint, in addition to clear preference for the female sex [2], clinical presentation and course differ between men and women with Cushing's disease. In fact, our first report on gender-dependent differences among these patients [3] was subsequently confirmed by other investigators [6][7][8][9]. Male patients with Cushing's disease usually present at a younger age, with more severe hypercortisolism and pronounced clinical features; hypogonadism induced by cortisol excess appears an important contributor to some clinical signs in males [8,39,40].…”
Section: Discussionsupporting
confidence: 58%
“…Male patients with Cushing's disease usually present at a younger age, with more severe hypercortisolism and pronounced clinical features; hypogonadism induced by cortisol excess appears an important contributor to some clinical signs in males [8,39,40]. As regards hormonal secretion, urinary free cortisol levels are higher in male patients with Cushing's disease [3,6] as occurs in normal adult men [41,42]; plasma ACTH concentrations follow the same pattern as higher levels have been observed in male patients [3,6,7,9], as well as in normal men [42,43]. Comparison of responses to diagnostic tests revealed that men with Cushing's disease are less likely to inhibit with the high dose dexamethasone test [3,7,8] and less likely to present positive pituitary magnetic resonance imaging [3,6]; in fact, inferior petrosal sinus sampling was required more frequently in men than women to confirm the pituitary lesion [44].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation